The use of social arithmetic contextual modules on learning achievement in terms of interest in learning - Winata, Rahmat; Permata, Jeliana Intan; Friantini, Rizki Nurhana (Department of Mathematics, Universitas Negeri Semarang, 2020)
This research aims to find out: (1) significant difference in students' mathematics achievement between the student who used the contextual social arithmetics module and who do not use it. (2) the difference in students' mathematics achievement among the student having high, medium, and low interest. (3) The interaction between contextual social arithmetics module and students' mathematics interest toward students' mathematics achievement. This research was quasi-experimental. The population of the study was the seventh grade of students of a Junior High School in West Borneo. The samples were 66 students. Data collection instruments using tests and questionnaires. The technique of analyzing the data was two-ways ANOVA. The results reveal that: (1) there is a significant difference in students' mathematics achievement between the student who used contextual social arithmetics module and students who do not use it. (2) there is a difference in students' mathematics achievement among students with high, medium, and low interest. (3) There is no interaction between the use of contextual social arithmetics module and students' mathematics interest toward students' mathematics achievement.